STEM-Blended Learning Regarding Earthquake Disaster: Prospective Teachers Perception - Didit Ardianto; Bibin Rubini; Indarini Dwi Pursitasari; Indriyani Rachman (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
This study aims to determine student teacher perceptions of the implementation of STEM-Blended learning. The subjects involved in this study consisted of 25 4th semester students in the elementary school teacher program. The instruments used include closed questionnaires and open questionnaires. The results showed that students gave a positive attitude towards scientific and engineering practices in the lecture process. In addition, they are also very motivated to create a prototype design that integrates STEM